Cannabinoid-dependent potentiation of inhibition at eye opening in mouse V1 - Garkun, Yury; Maffei, Arianna (Frontiers in Cellular Neuroscience, 2014)
Cannabinoid signaling is a well established regulator of synaptic transmission. Recent work demonstrated that cannabinoid release is necessary for the induction of inhibitory synaptic plasticity. In primary visual cortex (V1) cannabinoid receptors are present throughout life, though their level of expression is developmentally regulated. In the input layer of V1 (layer 4, L4) these receptors show low levels of expression and colocalize with GABAergic terminals suggesting that they may play an important role in regulating GABAergic transmission. Here we show that in the developmental window extending from eye opening to the onset of the critical period for visual cortical plasticity L4 inhibitory inputs onto pyramidal neurons are highly sensitive to activation of cannabinoid release. More specifically, application of synthetic and endogenous cannabinoid receptors agonists led to a significant increase in the amplitude and frequency of both spontaneous inhibitory postsynaptic currents (sIPSCs) and miniature inhibitory postsynaptic currents (mIPSC). This form of inhibitory potentiation is activity dependent, induced by repetitive bursting of pyramidal neurons and regulated by the time of eye opening. Cannabinoid dependent regulation of inhibitory drive may be a mechanism for the regulating L4 pyramidal neurons excitability and function at a time in which V1 transitions from being activated by spontaneous activity to being driven by visual inputs.